The Importance of Islamic Education in Forming Independent Persons - Armin, Muhammad (International Journal on Advanced Science, Education, and Religion, 2024)
Islamic education has become a major focus in character building and moral values in Muslim societies. In the context of globalization and the challenges of modern life, it is important to understand the role of Islamic education in shaping independent individuals. This study aims to explore the significance of Islamic education in shaping independent characters through a literature study approach with a library research method. The findings of the study indicate that Islamic education provides a strong moral foundation, teaches independence, and encourages the development of courage in individuals. Through religious values, individuals are taught to distinguish between right and wrong, take responsibility for their actions, and face challenges with a firm attitude. Thus, Islamic education has a crucial role in shaping individuals who are able to face the dynamics of life independently and courageously. This study provides new insights into the importance of Islamic education in the context of shaping independent individuals in the modern era.